“PEMBANGKANGAN” KEPALA DAERAH KEPADA MENTERI DI INDONESIA PADA ERA OTONOMI DAERAH - Mahmuzar Mahmuzar (Sultan Syarif Kasim State Islamic University, Riau, 2022)
The relationship between the local and central governments in the era of regional autonomy should be harmonious because the local government is a subsystem of the national government's that final responsibility lies with the President. In addition, one of the objectives of regional autonomy is to create harmonious relations between the central and local governments. But in fact, there are several regional heads in the Unitary State of the Republic of Indonesia which carried out